Use of Endobronchial Ultrasound to Evaluate Nonthrombotic Endovascular Lesions in Pulmonary Arteries. Issue 1 (January 2015) - Al-Saffar, Farah; Ibrahim, Saif; Seeram, Vandana; Bajwa, Abubakr A.; Shujaat, Adil
<x xml:space="preserve">Abstract</x> Background: The finding of a filling defect in a pulmonary artery (PA) sometimes raises the possibility of cancer. Endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration (TBNA) may confirm the underlying nature of the endovascular lesion. However, little is known about the use of this procedure for this purpose. Methods: We searched PubMed and abstracts of major international conferences. Results: There was a total of 12 cases: 8 female, 3 male, and 1 unknown. The median (range) age was 60 (51 to 79) years. EBUS was performed to evaluate mass-like lesion involving the PA (n=5), persistent or progressive filling defects in the PA despite anticoagulation (n=3), filling defect in the PA with multiple areas of consolidation, air-fluid levels in the lung (n=1), and hilar density (n=1). Moreover, an endovascular lesion was incidentally noted in the PA during EBUS for evaluating lymph nodes (n=2). EBUS-TBNA was diagnostic in 9 of the 10 cases in which it was performed. The final diagnoses were: sarcoma (n=6), lung cancer (n=2), thyroid cancer (n=1), renal cell cancer (n=1), melanoma (n=1), and pulmonary embolism (n=1). The cancer was a recurrence in 6 of the 7 cases with a known history of cancer. Conclusions: EBUS should be considered as a possible method for evaluating endovascular lesions when PA sarcoma or tumor macroembolism is suspected.